Fat Saturated Magnetic Resonance Imaging (Fs-MRI) in the Evaluation of Lumbar Facet Arthrosis in Adult Patients with Low Back Pain in a Teaching Hospital of Eastern Nepal - Khadka, Roshana; Dev, Binit; Bhattarai, Manoj (Birat Journal of Health Sciences, 2020)
Introduction: Facet joint arthropathy is one of the myriad of abnormalities for low back pain and since conventional Magnetic resonance Imaging detects the facet joint pathologies poorly when compared to fat suppressed MRI sequences, fat suppressed MRI promises to be contributory to proper diagnosis and management. Objective: The objective of this study was to find the prevalence of lumbar facet joint arthrosis among patients with low back pain and comparing conventional versus fat saturated sequence in detecting the MRI findings of facet joint arthrosis. Methodology: A cross sectional study was conducted at the Department of Radiodiagnosis and Department of Orthopedics at Birat Medical College Teaching Hospital from February 15, 2020 to May 15, 2020. Ethical clearance was taken and 100 participants having low back pain were enrolled for Magnetic Resonance imaging after informed consent. Data were Results: 57% study participants were found to have facet joint arthrosis (FJA) in their lumbar spine and on comparing the detection rate of the grades of arthrosis between the conventional and FS MRI, the difference in diagnosis of grade 2 and grade 3 changes of FJA were 87.9% and 42.9% respectively whereas no difference was found in diagnosing grade 4 changes in both the sequences. Data was entered in MS excel and analysed by SPSS. Conclusion: This study showed that facet joint arthrosis is frequently seen in the patients presenting with low back pain and these changes are better diagnosed by fat saturated MRI sequence as compared to conventional sequence.